Nonlinear methods in numerical analysis - Cuyt, Annie, 1956- (North-Holland mathematics studies ;, 1987)
While most textbooks on Numerical Analysis discuss linear techniques for the solution of various numerical problems, this book introduces and illustrates nonlinear methods. It presents several nonlinear techniques resulting mainly from the use of Pade approximants and rational interpolants.